Rural small scale industries and regional development: A Case Study From Bantul District, Special Province of Yogyakarta - With Stoffer; Agus Sutanto (Faculty of Geography, Universitas Gadjah Mada, 1990)
In last two decades, the small scale industrial sector, due to various reasons, has increasingly received attention from Indonesian policy makers. In the research area, rural small scale industrial activities play an important role, yet in a varying way. Production factors like labour and capital as well as the degree of localism are used to illustrate the differences in character.Attention is also paid to the linkages of those small scale industrial units with other units and sectors. Based on the main characteristics and the function of those rural small scale industrial activities, a distinction is made between basic and non-basic activities.A short description is given of the most important government programmes in the sphere of small scale industrial development. It is concluded that policy makers have given insufficient attention to the differences within the sector. As a result, most of the small scale industrial units are deprived of the programmes which are specifically designed for them.